2015
DOI: 10.1128/aem.03560-14
|View full text |Cite
|
Sign up to set email alerts
|

Two Phages, phiIPLA-RODI and phiIPLA-C1C, Lyse Mono- and Dual-Species Staphylococcal Biofilms

Abstract: Phage therapy is a promising option for fighting against staphylococcal infections. Two lytic phages, vB_SauM_phiIPLA-RODI (phiIPLA-RODI) and vB_SepM_phiIPLA-C1C (phiIPLA-C1C), belonging to the Myoviridae family and exhibiting wide host ranges, were characterized in this study. The complete genome sequences comprised 142,348 bp and 140,961 bp and contained 213 and 203 open reading frames, respectively. The gene organization was typical of Spounavirinae members, with long direct terminal repeats (LTRs), genes g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
136
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(147 citation statements)
references
References 70 publications
10
136
1
Order By: Relevance
“…In a previous study performed in our laboratory, we described that treatment with phiIPLA-RODI reduced the number S. aureus IPLA16 cells by 2.4 log units in monospecies biofilms and by 4.2 log units in dual-species biofilms formed with the phagesensitive strain S. epidermidis LO5081 (15). Thus, the presence of a second species, also susceptible to the phage, seemed to enhance the efficacy of phage treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study performed in our laboratory, we described that treatment with phiIPLA-RODI reduced the number S. aureus IPLA16 cells by 2.4 log units in monospecies biofilms and by 4.2 log units in dual-species biofilms formed with the phagesensitive strain S. epidermidis LO5081 (15). Thus, the presence of a second species, also susceptible to the phage, seemed to enhance the efficacy of phage treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For selective growth of the different species, the following media were used: Baird-Parker agar (BP) for S. aureus, Kenner Fecal (KF) agar for E. faecium, and MRS agar plates for the other three strains. Bacteriophage phiIPLA-RODI was propagated on S. aureus IPLA1 as previously described (15).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have also been shown to clear biofilm infections caused by P. aeruginosa (41). Two lytic phages were recently described that were found to reduce Staphylococcal biofilms by 2 logs and the frequency of bacteriophage resistance developing in the bacteria was sufficiently low to merit these bacteriophages as potential candidates for therapy (42). Another recent study found a bacteriophage, EFDG1, to have effective lytic activity against planktonic and biofilm cultures of Enterococcus faecalis and E. faecium isolates, regardless of their antibiotic resistance profile (43).…”
Section: Bacteriophage Therapy To Fight Biofilm Infectionsmentioning
confidence: 99%